‘Neglected’ macrolithic toolkits: polishing pebbles from the Neolithic sites of Avgi and Makri, Northern Greece - Bekiaris , Tasos (Journal of Greek Archaeology, 2024)
During the last twenty years, or so, macrolithic artifacts (also known as ground stones), a rather significant but neglected category of the prehistoric material culture, have begun to attract global academic interest. The relevant literature is rapidly expanding, as new macrolithic data from sites all over the world are constantly emerging. Moreover, radical developments in the field of methodology, including the application of innovative analytical techniques (e.g., petrography, geochemistry, use-wear, micro-botany, experimentation), and challenging theoretical concepts (e.g., network theory, entanglement, biographical approach, technology) have altered the former ‘static’ view of the macrolithics, and shed new light on the ‘dynamic’ character and varied meaning that these artifacts held for the communities of the past. The Aegean area was not excluded from this global advancement of macrolithic studies. Several assemblages, some of which are counting thousands of artifacts, became the focus of systematic and often interdisciplinary research. Innovative methodological protocols and state-of-the-art analytical techniques have been applied, thus leading to the formation of a rather significant corpus of publications regarding macrolithic implements of the Prehistoric Aegean.